Nutrient Adequacy of Beef Cattle in Coastal Areas Kumai Sub-District, West Kotawaringin District - Pujiastuti, Asih (Journal of Tropical Animal Science and Technology, 2024)
This study aims to determine the nutrient adequacy of beef cattle in the coastal area of ​​Kumai District. The study was carried out from February – March 2022 in six coastal villages of ​​Kumai District, West Kotawaringin Regency. The six villages were Sabuai villages, Sebuai Timur villages, Keraya villages, Teluk Bogam villages, Sungai Bakau villages, and Kubu villages. BK analysis at the Animal Production Laboratory, Faculty of Agriculture, Antakusuma University, while Ca and P analysis at the Animal Food Science Laboratory, Gadjah Mada University (UGM). There were 60 beef cattle used, each village used 10 beef cattle were selected purposively. The parameters observed included consumption of BK, PK, Ca, P and body weight. The data obtained in this study was analyzed descriptively. The result showed that the average body weight in six village was 311, 75 kg. The average consumption of DM was 7,76 kg/head/day, CP 516,06 g/head/day, Ca 21,18 g/head/day dan P 2,81 g/head/day. While the average requirement of DM was 6,24 kg/head/day, CP 604,68 g/head/day, Ca 15,26 g/head/day, dan P 12,11 g/head/day. Based on the result of the study, it can be concluded that the feed given to beef cattle was sufficient for the nutrient requirements of BK and Ca, while PK and P was not sufficient for the nutrient requirements of beef cattle.